Electrolyzed water oxygen evolution catalytic electrode and preparation process thereof

By oxalic acid etching and sodium oxalate modification of foam nickel, electrolytic oxygen-analyzed catalytic electrodes were prepared in combination with the electrodeposition process, which solved the problems of uneven catalytic performance, poor process repeatability and poor stability of the existing electrode sheets, and achieved efficient, uniform and stable catalytic effects in the electrolytic hydrogen production process.

CN119615226AActive Publication Date: 2025-03-14NANTONG HEFAN ENERGY TECHNOLOGY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510158277.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The existing electrode sheets have uneven catalytic performance, poor process repeatability and poor stability during the electrolytic hydrogen production process, making it difficult to meet the high requirements of the market for hydrogen production efficiency.

Method used

After etching the foam nickel with oxalic acid, surface modification is performed using sodium oxalate to form a modified substrate, and electrodeposited with the nickel mesh anode and the electrodeposition solution, an electrolytic oxygen-excitation catalytic electrode was prepared.

Benefits of technology

The catalytic performance distribution of the electrolytic oxygen-analyzed catalytic electrode is achieved, with high process repeatability and good stability, and the efficiency and reliability in the electrolytic hydrogen production process is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615226A_ABST
    Figure CN119615226A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolytic water oxygen evolution catalytic electrode and a preparation process thereof, and relates to the field of electrode materials. When the water electrolysis oxygen evolution catalytic electrode is prepared, foamed nickel is etched through oxalic acid, then sodium oxalate is used for surface modification, and a modified substrate is obtained; and carrying out electro-deposition on the modified substrate, a nickel net anode and the electro-deposition solution to prepare the catalytic electrode for oxygen evolution by electrolysis of water. The water electrolysis oxygen evolution catalytic electrode prepared by the invention has excellent stability, catalytic uniformity and process repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrode materials, and in particular to a catalytic electrode for oxygen evolution by water electrolysis and a preparation process thereof. Background Art

[0002] Hydrogen energy, as the most ideal energy carrier, is becoming the focus of people's attention, and the green production of hydrogen energy has also become the key to the future research and development of hydrogen energy technology. Hydrogen production by water electrolysis, combined with renewable energy power generation systems represented by photovoltaics and wind power, can provide an ideal technical means for the sustainable supply of hydrogen energy in the future. Anion exchange membrane water electrolysis (AEM) technology has attracted much attention as a clean and sustainable way of hydrogen production and renewable energy conversion. The electrolyzer is an important component of AEM system technology. The core components are divided into anode electrode sheets and cathode electrode sheets, which function to catalyze oxygen production and hydrogen production respectively. The oxygen evolution process is the key reaction that determines the efficiency of water electrolysis.

[0003] As the market demand for hydrogen energy continues to increase, the market has higher and higher requirements for the hydrogen production efficiency of electrode sheets. Common methods for making electrode sheets mainly include surface coating and bonding methods, among which the surface catalytic performance of the electrode sheets prepared by the surface coating and bonding methods is uneven, the process repeatability is poor, and the stability in the long-term electrolysis of water to produce hydrogen is poor. Therefore, the present invention prepares a catalytic electrode for electrolysis of water and oxygen evolution with good stability, uniform catalytic performance distribution and high process repeatability. Summary of the invention

[0004] The object of the present invention is to provide a catalytic electrode for oxygen evolution by water electrolysis and a preparation process thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention discloses a catalytic electrode for oxygen evolution by electrolysis of water. The catalytic electrode for oxygen evolution by electrolysis of water is prepared by electrodeposition of a modified substrate, a nickel mesh anode and an electrodeposition solution.

[0006] As an optimization, the modified substrate is obtained by etching nickel foam with oxalic acid and then surface-modifying it with sodium oxalate.

[0007] A preparation process of a catalytic electrode for oxygen evolution by water electrolysis, comprising the following preparation steps: (1) The nickel foam is ultrasonically treated in deionized water at 20-30°C for 3-10 minutes, then taken out, immersed in a 0.1-5 mol / L oxalic acid solution for etching for 23-25 ​​hours, and then cleaned with deionized water spray for 3-10 minutes, and then immersed in a 0.1-1 mol / L sodium oxalate solution again, kept at 40-60°C for 3-6 hours, and then taken out and cleaned with deionized water spray for 4-6 minutes to obtain a modified substrate; (2) Mix ferric nitrate, nickel nitrate, oxalic acid and deionized water to obtain an electrodeposition solution; place the modified substrate and the nickel mesh anode in parallel in an electroplating box, add the electrodeposition solution, and conduct the electroplating at 10-100 mA / cm 2 The electrode was deposited for 60-300 seconds and cleaned with deionized water mist spray for 5-10 minutes to obtain a catalytic electrode for oxygen evolution by water electrolysis.

[0008] As an optimization, the Fe in the electrodeposition solution in step (2) 3+ The concentration is 0.06mol / L.

[0009] As an optimization, the Ni in the electrodeposition solution in step (2) 2+ The concentration is 0.24mol / L.

[0010] As an optimization, the oxalic acid concentration in the electrodeposition solution in step (2) is 0.0075 mol / L.

[0011] As an optimization, the vertical distance between the modified substrate and the nickel mesh anode in step (2) in the electroplating box is 3 to 10 cm.

[0012] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the electrolytic water oxygen evolution catalytic electrode, the present invention etches the foamed nickel with oxalic acid and then performs surface modification with sodium oxalate to obtain a modified substrate; and then performs electrodeposition on the modified substrate, a nickel mesh anode and an electrodeposition solution to obtain the electrolytic water oxygen evolution catalytic electrode.

[0013] First, the nickel foam is etched with oxalic acid and then surface modified with sodium oxalate to obtain a modified substrate. The surface etching modification process forms a microscopic rough surface on the nickel foam to increase the specific surface area of ​​the nickel foam. At the same time, oxalate ions are introduced to form a complex with the metal ions on the surface of the nickel foam to promote the Ni electrodeposition process. 2+ and Fe 3+ The ions are adsorbed on the surface of nickel foam to form amorphous, microporous and uniform non-crystalline high-performance NiFeOOH, which improves the catalytic uniformity and stability of the catalytic electrode for oxygen evolution in water electrolysis.

[0014] Secondly, the modified substrate, nickel mesh anode and electrodeposition solution are electrodeposited to obtain a catalytic electrode for oxygen evolution by electrolysis of water; the slightly acidic environment formed by oxalic acid in the electrodeposition process can remove the catalyst with poor binding force on the surface of the modified substrate. At the same time, during the cathode deposition reduction process, the catalyst surface is regulated to expose more active sites, thereby increasing the electrochemical performance; compared with the traditional coating and bonding methods of physical adsorption, the catalytic layer prepared by electrodeposition has stronger adsorption stability, mature technology, wide applicability and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a process diagram of the electrode sheet of the catalytic electrode for oxygen evolution by electrolysis of water described in the present invention.

[0016] Figure 2 This is a scanning electron microscope image of the amorphous α-NiFeOOH on the water electrolysis oxygen evolution catalytic electrode described in the present invention.

[0017] Figure 3 This is a transmission electron microscope image of the amorphous α-NiFeOOH on the water electrolysis oxygen evolution catalytic electrode described in the present invention.

[0018] Figure 4 This is a test diagram of the oxygen evolution performance of different oxygen evolution electrodes in the three-electrode system of the water electrolysis oxygen evolution catalytic electrode described in the present invention.

[0019] Figure 5 This is a stability test diagram of the water electrolysis oxygen evolution catalytic electrode described in the present invention in the self-developed AEM electrolyzer.

[0020] Figure 6 This is a test diagram of the electrode sheet uniformity of the catalytic electrode for oxygen evolution by water electrolysis described in the present invention.

[0021] Figure 7 This is a process repeatability test diagram of the catalytic electrode for oxygen evolution by water electrolysis described in the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The nickel foam described below comes from Kunshan Jiayisheng Electronics Co., Ltd.; the nickel mesh anode comes from Hebei Kangwei Metal Products Co., Ltd.; Example

[0024] A preparation process of a catalytic electrode for oxygen evolution by electrolysis of water, the preparation process of the catalytic electrode for oxygen evolution by electrolysis of water comprising the following preparation steps: (1) A 50 cm × 50 cm nickel foam was placed in 25°C deionized water for 5 min and then taken out, immersed in a 2 mol / L oxalic acid solution for etching for 24 h, and then cleaned with deionized water spray for 5 min. It was then immersed in a 0.5 mol / L sodium oxalate solution again and kept at 50°C for 4.5 h. After being taken out, it was cleaned with deionized water spray for 5 min to obtain a modified substrate. (2) Mix ferric chloride, nickel nitrate, oxalic acid and deionized water to obtain an electroplating solution; place the modified substrate and the nickel mesh anode in parallel in an electroplating box, add the electroplating solution, and 2 After deposition for 100 seconds, the electrode was cleaned with deionized water mist spray for 7 minutes to obtain a catalytic electrode for oxygen evolution by water electrolysis.

[0025] The Fe in the above electrodeposition solution 3+ The concentration is 0.06mol / L, Ni 2+ The concentration is 0.24mol / L and the concentration of oxalic acid is 0.0075mol / L.

[0026] Test Example 1: Surface morphology Test method: The electrolytic water oxygen evolution catalytic electrode obtained in the example was tested by scanning electron microscope (refer to Figure 2 ) and transmission electron microscopy (ref. Figure 3 ).

[0027] Depend on Figure 2 It can be seen that the etching modification process makes the nickel foam form a microscopic rough surface, the specific surface area increases, and the introduced oxalate ions form a complex with the metal ions on the surface of the nickel foam. 2+ and Fe 3+ The microscopic porous and uniform amorphous high-performance NiFeOOH formed by ions adsorbed on the surface of nickel foam is in an amorphous state; Figure 3 It can be seen that the Ni, Fe and O elemental components in the electrolytic water oxygen evolution catalytic electrode obtained in the example are uniformly distributed, and no diffraction spots or diffraction rings are found in the diffraction test, indicating that the catalyst is amorphous.

[0028] Test Example 2: Oxygen Evolution Performance Test method: Take 1cm*1cm test samples of the water electrolysis oxygen evolution catalytic electrode obtained in the example, the commercially available NiFe-LDH catalyst, the nickel foam substrate and the Raney nickel electrode, respectively, and test the oxygen evolution performance in a three-electrode system (the counter electrode is a platinum sheet, the reference electrode is Hg / HgO, and the electrolyte is a 1 mol / L potassium hydroxide solution) (refer to Figure 4 ).

[0029] Depend on Figure 4 It can be seen that the amorphous a-NiFeOOH has low internal resistance, high oxygen production efficiency, and catalytic performance higher than that of the NiFe-LDH catalyst prepared by traditional electrodeposition, and also higher than that of the foam nickel substrate and the Raney nickel electrode commonly used in traditional ALK cells.

[0030] Test Example 3: Stability Test method: The electrolytic water oxygen evolution catalytic electrode obtained in the example was cut into test samples of 5cm*5cm size, and the cell pressure attenuation was tested using a self-made AEM electrolytic water hydrogen production cell (effective reaction area 5cm*5cm) at 1A / cm², 60℃, and 1mol / L potassium hydroxide solution (refer to Figure 5 ).

[0031] Depend on Figure 5 It can be seen that the single cell voltage of the water electrolysis oxygen evolution catalytic electrode obtained in the embodiment can reach 1.92V, and no obvious attenuation of the cell voltage was found after testing for 320h, which has good stability.

[0032] Test Example 4: Catalytic Performance Uniformity Test method: The electrolytic oxygen evolution catalytic electrode obtained in the example was cut into 10 pieces of 1 cm*1 cm samples at different positions. The catalytic performance of the samples was tested in a three-electrode system (the counter electrode was a platinum sheet, the reference electrode was Hg / HgO, and the electrolyte was a 1 mol / L potassium hydroxide solution). The difference between the sample and the average catalytic performance was calculated = (sample catalytic performance - average catalytic performance) / average catalytic performance * 100% (reference Figure 6 ).

[0033] Depend on Figure 6 It can be seen that the oxygen evolution performance of the water electrolysis oxygen evolution catalytic electrode obtained in the embodiment differs from the average value by + / - 5% at different positions. Compared with the traditional coating method and bonding method, the process combining surface etching modification and electrodeposition makes the catalytic layer of the electrode sheet more evenly distributed.

[0034] Test Example 5: Process Repeatability Test method: Take the different batches of water electrolysis oxygen evolution catalytic electrodes obtained in the example, cut out 1cm*1cm test samples at the same position, test the catalytic performance of the samples in a three-electrode system (the counter electrode is a platinum sheet, the reference electrode is Hg / HgO, and the electrolyte is a 1 mol / L potassium hydroxide solution), and calculate the difference between the average value = (sample catalytic performance-average catalytic performance) / average catalytic performance*100% (reference Figure 7 ).

[0035] Depend on Figure 7 It can be seen that the oxygen evolution performance of the catalytic electrodes for oxygen evolution by water electrolysis of different batches obtained in the embodiment differs from the average value by + / - 5% at the same position. Compared with the traditional coating method and bonding method, the process repeatability of the surface etching modification process combined with electrodeposition is high, and the performance difference between batches of catalytic electrode sheets is small.

[0036] from Figures 2 to 7By comparing the experimental data in , it can be found that the catalytic electrode for oxygen evolution by water electrolysis prepared by the present invention has good stability, catalytic uniformity and process repeatability.

[0037] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A catalytic electrode for oxygen evolution by water electrolysis, characterized in that: The electrolytic water oxygen evolution catalytic electrode is prepared by electrodeposition of a modified substrate, a nickel mesh anode and an electrodeposition solution; The modified substrate is obtained by etching nickel foam with oxalic acid and then performing surface modification with sodium oxalate.

2. A process for preparing a catalytic electrode for oxygen evolution by water electrolysis, characterized in that: The method comprises the following preparation steps: (1) The nickel foam is ultrasonically treated in deionized water at 20-30°C for 3-10 minutes, then taken out, immersed in a 0.1-5 mol / L oxalic acid solution for etching for 23-25 ​​hours, and then cleaned with deionized water spray for 3-10 minutes, and then immersed in a 0.1-1 mol / L sodium oxalate solution again, kept at 40-60°C for 3-6 hours, and then taken out and cleaned with deionized water spray for 4-6 minutes to obtain a modified substrate; (2) Mix ferric chloride, nickel nitrate, oxalic acid and deionized water to obtain an electrodeposition solution; place the modified substrate and the nickel mesh anode in parallel in an electroplating box, add the electrodeposition solution, and 2 The electrode was deposited for 60-300 seconds and cleaned with deionized water mist spray for 5-10 minutes to obtain a catalytic electrode for oxygen evolution by water electrolysis.

3. The preparation process of a catalytic electrode for oxygen evolution by water electrolysis according to claim 2, characterized in that: Fe in the electrodeposition solution of step (2) 3+ The concentration is 0.06mol / L.

4. The process for preparing a catalytic electrode for oxygen evolution by water electrolysis according to claim 2, characterized in that: In step (2), Ni in the electrodeposition solution 2+ The concentration is 0.24mol / L.

5. The preparation process of a catalytic electrode for oxygen evolution by water electrolysis according to claim 2, characterized in that: The concentration of oxalic acid in the electrodeposition solution in step (2) is 0.0075 mol / L.

6. The process for preparing a catalytic electrode for oxygen evolution by water electrolysis according to claim 2, characterized in that: In step (2), the vertical distance between the modified substrate and the nickel mesh anode in the electroplating box is 7 cm.

7. The process for preparing a catalytic electrode for oxygen evolution by water electrolysis according to claim 2, characterized in that: The size of the nickel mesh anode in step (2) is the same as that of the modified substrate.

Citation Information

Patent Citations

  • Preparation method of foamed nickel carrier palladium iridium electrode

    CN103280585A

  • Three-dimensional nickel-iron layered dihydroxide array as well as room temperature preparation method thereof and application thereof

    CN108716008A

  • A preparing method for a foamed nickel-ferronickel oxide composite oxygen evolution catalyst

    CN109201060A

  • Preparation and application of NiFeOxHy oxygen evolution catalyst with easily oxidizable Ni<2+>

    CN114086209A

  • Universal method for preparing self-supporting layered metal hydroxide

    CN114134531A